2014
DOI: 10.2478/aoter-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

A study of thermal diffusivity of carbon-epoxy and glass-epoxy composites using the modified pulse method

Abstract: Transient heat transfer is studied and compared in two planeparallel composite walls and one EPIDIAN 53 epoxy resin wall acting as a matrix for both composites. The first of the two walls is made of carbonepoxy composite; the other wall is made of glass-epoxy composite, both with comparable thickness of about 1 mm and the same number of carbon and glass fabric layers (four layers). The study was conducted for temperatures in the range of 20-120 o C. The results of the study of thermal diffusivity which charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Figure 13 shows that the T g(0) values are very similar for the CFRP, GFRP, and resin specimens, with small heating rate differences. Terpilowski et al 20 found the thermal diffusivity of CFRP to be higher than GFRP, from which it would be expected that the heating rate dependence would be lower for the CFRP specimens (i.e. a reduced thermal lag).…”
Section: Effect Of Fiber Reinforcement Type On T G Measurement (Systementioning
confidence: 99%
“…Figure 13 shows that the T g(0) values are very similar for the CFRP, GFRP, and resin specimens, with small heating rate differences. Terpilowski et al 20 found the thermal diffusivity of CFRP to be higher than GFRP, from which it would be expected that the heating rate dependence would be lower for the CFRP specimens (i.e. a reduced thermal lag).…”
Section: Effect Of Fiber Reinforcement Type On T G Measurement (Systementioning
confidence: 99%
“…Since the polymer matrix essentially needs to resist higher loads, it is normally reinforced with fibers and fillers. Polymer composites reinforced with synthetic fibers made up of glass [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], carbon [21][22][23][24][25][26][27][28][29][30], aramid [31][32][33][34] etc. are being extensively deployed in engineering applications because of their exceptional mechanical performance.…”
Section: Introductionmentioning
confidence: 99%